Analysis Of Students’ Internal Problems In The Seminar Proposals A The English Department Of Madako University - Pajrul (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
This study aims to examine the internal challenges faced by eighth-semester students of the English Department at Madako University in writing their seminar proposals. The research employs a descriptive qualitative method, using semi-structured interviews as the data collection technique involving eight students as respondents. The findings reveal three main problems experienced by the students: low levels of motivation, poor time management, and limited writing and research skills. These issues significantly affect the proposal writing process, leading to procrastination, increased stress, delays in task completion, and difficulties in producing coherent and well-structured academic writing. In addition, these conditions also influence students’ confidence in developing scientific work that meets academic standards. Therefore, this study recommends the provision of more intensive academic support from the university, as well as specific training in time management and the development of writing and research skills. These efforts are expected to help students complete their seminar proposals more effectively, efficiently, and on time.